Circadian rhythm disruptions: A possible link of bipolar disorder and endocrine comorbidities - Yan, Xiu; Xu, Peiwei; Sun, Xueli (Frontiers in Psychiatry, 2023)
Epidemiological studies have demonstrated an association between bipolar disorder and endocrine diseases. Further, circadian rhythm disruptions may be a potential common pathophysiological mechanism of both disorders. This review provides a brief overview of the molecular mechanisms of circadian rhythms, as well as roles circadian rhythms play in bipolar disorder and common endocrine comorbidities such as diabetes and thyroid disease. Treatments targeting the circadian system, both pharmacological and non-pharmacological, are also discussed. The hope is to elicit new interest to the importance of circadian system in bipolar disorder and offer new entry points and impetus to the development of medicine.